Artificial Biocatalytic Cascade with Three Enzymes in One Pot for Asymmetric Synthesis of Chiral Unnatural Amino Acids. Issue 38 (26th September 2019) - Zhou, Haisheng; Meng, Lijun; Yin, Xinjian; Liu, Yayun; Xu, Gang; Wu, Jianping; Wu, Mianbin; Yang, Lirong
Abstract : Two biocatalytic reactions, transamination catalyzed by transaminases and reductive amination catalyzed by amino acid dehydrogenases, can be used for asymmetric synthesis of optically pure unnatural amino acids. However, although transaminases show a great diversity and broad substrate spectrum, most transaminase reactions are reversible, while amino acid dehydrogenases catalyze reductive amination irreversibly but with strict substrate specificity. Accordingly, herein we developed a tri‐enzyme one‐pot reaction system to exploit the respective advantages of transaminases and amino acid dehydrogenases, while overcoming the disadvantages of each. In this work, representatives of all four subgroups of transaminases coupled with different amino acid dehydrogenases to produce five l ‐ and four d ‐ unnatural amino acid products, using ammonia and the co‐enzyme NAD(P)H, which is regenerated by a robust alcohol dehydrogenase with 2‐propanol as cheap cosubstrate. The complete conversion and high enantiopurity (ee > 99 %) of the products, demonstrated it as an ideal alternative for asymmetric synthesis of chiral amino acid compounds. Abstract : An artificial biocatalytic cascade for asymmetric synthesis of optically pure unnatural amino acids was developed. This method employed three kinds of enzyme in one‐pot reaction, with great flexibility of the enzyme combination, exhibited a broad substrate spectrum. Using only a catalytic amount of amino donor, the reaction can reach complete conversion with high enan‐tiopurity of both d ‐ and l ‐ products.